Protein kinase associated with ribosomes of streptomycetes - Mikulík, K; Zhoulanova, E; Hoang, Q K; Janecek, J; Bezousková, S (Folia microbiologica, 1999)
Protein kinases can be classified into two main superfamilies on the basis of their sequence similarity and substrate specificity. The protein His kinase superfamily which autophosphorylate a His residue, and superfamily Ser/Thr and Tyr protein kinases, which phosphorylate Ser, Thr or Tyr residues. During the last years genes encoding Ser/Thr protein kinases have been identified in several microorganisms. Phosphorylation of proteins on Ser/Thr residues can be involved in many functions of prokaryotic cells including cell differentiation, signal transduction and protein biosynthesis. Phosphorylation of prokaryotic protein-synthesizing systems showed that the phosphorylation of initiation and elongation factors is subject to alteration during cell differentiation or bacteriophage infection. Protein kinase associated with ribosomes of streptomycetes phosphorylate the elongation factor Tu and 11 ribosomal proteins even in bacteriophage-uninfected cells. After phosphorylation of ribosomal proteins, ribosomes lose about 30% of their activity at the translation of poly(U).
Keywords: proteinkinasy; ribozomy; ribozomální proteiny; sekvence aminokyselin; Molecular Sequence Data; Peptide Elongation Factor Tu; Bacterial Proteins; Phosphorylation; elongační faktor Tu; molekulární sekvence - údaje; Protein Kinases; Ribosomal Proteins; Amino Acid Sequence; Streptomyces; bakteriální proteiny; fosforylace; Ribosomes